Psycho-Educational Program sebagai Strategi Peningkatan Partisipasi Lansia pada Program Prolanis di Puskesmas Tamalanrea Makassar - Hastuti, Hastuti; Harisa, Akbar; Gaffar, Indra; Rahman, Framita; Fitriani, Nurlaila; Darwis, A Muflihah; Bakhtiar, Hasmiranda; Amila R, May Shafarah; Nafs, Ummul Tazkiyatun; Yodang, Yodang; Abduh, Sahrina (Universitas Baiturrahim, 2024)
In Indonesia, the elderly with chronic illnesses have a relatively high percentage. According to the Basic Health Research (Riskesdas) results in 2018, data indicates an increase in non-communicable diseases such as diabetes, hypertension, and stroke among the elderly. The aging process in the elderly leads to a decline in physiological body functions, resulting in the emergence of non-communicable diseases in old age. The purpose of this community service activity is to enhance the knowledge of the elderly about chronic diseases (hypertension and type II diabetes) through a psycho-educational approach. The educational methods employed include lectures, counseling, and discussions. This activity took place on Friday, September 8, 2023, and was attended by 32 elderly individuals at the Tamalanrea Community Health Center who participated voluntarily. Based on observations, the majority of the elderly demonstrated good knowledge about chronic diseases after the question-and-answer sessions and discussions between the speakers and participants. It is hoped that through this activity, the community, especially the elderly, will gain a better understanding of chronic diseases (hypertension and type II diabetes), leading to behavioral changes and improved capabilities in identifying and preventing chronic illnesses in the future.